Biosynthesis of plant tetrahydroisoquinoline alkaloids through an imine reductase route. Issue 2 (29th November 2019) - Yang, Lu; Zhu, Jinmei; Sun, Chenghai; Deng, Zixin; Qu, Xudong
Abstract : An artificial approach has been developed for efficient biosynthesis of plant tetrahydroisoquinoline alkaloids from dihydroisoquinoline precursors. Abstract : Herein, we report a biocatalytic approach to synthesize plant tetrahydroisoquinoline alkaloids (THIQAs) from dihydroisoquinoline (DHIQ) precursors using imine reductases and N -methyltransferase (NMT). The imine reductase IR45 was engineered to significantly expand its substrate specificity, enabling efficient and stereoselective conversion of 1-phenyl and 1-benzyl 6, 7-dimethoxy-DHIQs into the corresponding ( S )-tetrahydroisoquinolines ( S -THIQs). Coclaurine N -methyltransferase (CNMT) was able to further efficiently convert these ( S )-THIQ intermediates into ( S )-THIQAs. By assembling IRED, CNMT, and glucose dehydrogenase (GDH) in one reaction, we effectively constituted two artificial biosynthetic pathways in Escherichia coli and successfully applied them to the production of five ( S )-THIQAs. This highly efficient (100% yield from DHIQs) and easily tailorable (adding other genes) biosynthetic approach will be useful for producing a variety of plant THIQAs.